Power quality grid code compliance for renewable power plants in South Africa. Issue 1 (7th December 2018) - Minnaar, Ulrich John; Peterson, Brandon; Mostert, Hennie; Rens, Johan; Botha, Gerhard
Abstract : The introduction of renewable generation to South Africa's grid has introduced challenges to the management and regulation of power quality (PQ). These have been addressed by establishing PQ compliance criteria in line with local circumstances and by the introduction of a Power Quality Guideline for renewable power plants (RPPs). A key challenge to RPPs has been meeting emission limits for harmonics. This has been addressed in South Africa's RPP Guideline by the development and introduction of a Group Harmonic Distortion limit which provides some flexibility to RPPs in making individual harmonic emission limits. The use of 95th percentile harmonic impedance envelopes is discussed and recommendations for impedance envelopes are made for different voltage levels within the South African Grid, based on actual network data. A lesson learnt is that using international standards and guidelines provides a starting point for compliance rules when introducing renewable generation. Developing countries that share economic and electricity network characteristics with South Africa should tailor the PQ rules and guidelines for RPPs to meet local conditions.